The Impact of Leadership Style, Organizational Climate, Motivation, and Culture on Teachers’ Performance - Derizald Derizald; Yulina Eliza; Sumiati Sumiati (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2026)
This study investigates the influence of leadership style, organizational climate, motivation, and organizational culture on teachers’ performance at SMA Negeri 1 Basa Ampek Balai. A quantitative research design was adopted, employing a survey method through the distribution of structured questionnaires to 50 teacher respondents. The collected data were processed using descriptive statistical analysis, classical assumption testing, and multiple linear regression analysis with the support of IBM SPSS version 26.0. The results of the descriptive analysis reveal that teachers’ performance, leadership style, motivation, and organizational culture are generally perceived at a good level, whereas the organizational climate is assessed as moderately good. The normality test indicates a significance value of 0.074, exceeding the standard threshold of 0.05, which confirms that the data are normally distributed. The partial hypothesis testing (t-test) demonstrates that leadership style, organizational climate, motivation, and organizational culture each exert a positive and statistically significant effect on teachers’ performance. In addition, the simultaneous hypothesis testing using the F-test (ANOVA) yields a significance value of 0.000, indicating that all independent variables collectively have a significant influence on teachers’ performance. Furthermore, the coefficient of determination (R²) is recorded at 0.717, suggesting that 71.7% of the variance in teachers’ performance can be explained by the combined effects of leadership style, organizational climate, motivation, and organizational culture, while the remaining 28.3% is attributed to other factors beyond the scope of this study. These findings emphasize the strategic role of school leadership in fostering a supportive organizational environment, strengthening motivation, and cultivating a positive organizational culture to enhance teachers’ performance. This study contributes valuable empirical evidence to the field of educational management, particularly within public senior high schools in regional contexts.